Evaluation of Digital Technology Management in Mathematics Learning: A Sequential Explanatory Design in Eastern Indonesia - Fitrah, Muh.; Caly Setiawan; Widihastuti; Marinding, Yudince; Herianto (Nordic Journal of Comparative and International Education (NJCIE), 2024)
The rapid advancement of digital technology necessitates that teachers enhance their competencies in the teaching and learning process of mathematics. This study aims to evaluate the demographic factors affecting teachers' use of digital technology and their digital skills, explore the frequency of online learning platform usage in relation to teachers' digital skills, and identify challenges while providing recommendations for integrating technology into mathematics instruction through a Sequential Explanatory Design mixed-methods approach. The quantitative sample consisted of 104 mathematics teachers, with 14 teachers selected as respondents for the qualitative phase. Data collection instruments included questionnaires, structured interviews, and non-participant observations, with quantitative data analyzed using Jamovi 2.4.8.0 software, and qualitative data manually coded and thematically analyzed using an inductive-deductive approach. The findings indicate that employment status, teaching experience, and school level significantly influence the use of digital technology in teaching mathematics. Teachers who are government employees under contract, have over 10 years of teaching experience, and teach at the middle or high school level tend to integrate technology more effectively. Consequently, government policies and educational programs for technology development should prioritize teachers irrespective of their employment status, offering continuous training (both online and offline) focused on mathematics.